Karawitan Pakeliran Gaya Jawa Timuran - Asal Sugiarto (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
East Java’s music for wayang style. East Java’s music for wayang style has its own characteristics that distinguishfrom other styles, such as Yogyakarta and Surakarta’s style. This paper describes a typical characteristic East Javamusic for wayang using qualitative methods. The elements covered including the structure and function (music forwayang, mood song, gedhogan, and kepyak). Based on the observation can be concluded that Gandakusuma SlendroPatet Nem peace is music used for the fi rst scene in all character and country. In addition, East Java music forwayang use four mode ( pathet), i.e. sepuloh mode, wolu mode, sanga mode, and serang mode.